(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2015)
This paper presents an analysis of master’s programs that currently exist in Colombia to provide education in the field of computing. For performing this work, a four steps methodology was used: i) identification of the academic offer, ii) recompilation of information, iii) classification of the programs iv) and generation of reports and analysis of the findings. The main results are the characterization of the academic offer of master programs in computing, the names of the programs, their granted academic degrees, and the research areas, which were analyzed and classified by taking as reference the curricula recommendations by the Association for Computing Machinery - ACM. Finally, this study provides elements that enrich the ongoing discussion that occurs in the academic community in the country, on the present and future of computer education at different levels, and particularly in the master level.